Fusing 10-vertex closo-carborane anions with N-heterocyclic carbenes. Issue 75 (8th September 2022) - Tej Raviprolu, Varun; McArthur, Sarah E.; Banda, Isaac; Gregory, Aaron; McArthur, Scott G.; Fisher, Steven P.; Lavallo, Vincent
Abstract : Discovered by Knöth in 1964, the 10-vertex closo -carborane anion [HCB9 H9 1− ] is a classical bicapped square antiprism that contains an unusual pentacoordinate carbon center. Abstract : Discovered by Knöth in 1964, the 10-vertex closo -carborane anion [HCB9 H9 1− ] is a classical bicapped square antiprism that contains an unusual pentacoordinate carbon center. Compared to its larger icosahedral cousin [HCB11 H11 1− ], few investigations have been made into its use as a weakly coordinating anion or as a ligand substituent. Here we show that it is possible to prepare both a dianionic N-heterocyclic carbene (NHC) Li + adduct as well as a trianionic C-2, C-5 dilithio species featuring two 10-vertex carborane anion substituents. All compounds were characterized via multinuclear NMR spectroscopy, single crystal X-ray diffraction, and HRMS when possible.